Sid the science kid. Weather kid Sid - Henson, Jim.; NCircle Entertainment ([United States] : Distributed by NCircle Entertainment, 2009)
Sid's not too happy when rain threatens to squash his play date outside. But the more Sid learns about the rain, the more he understands how important precipitation is! In fact, Sid is learning about all the weather conditions and how they affect our world.
Sid's rainy play date -- Special sunny Dad day -- Sid's holiday adventure -- The wind did it.
Originally broadcast as episodes of the television program.
Title from container.
"PBS kids"
DVD, NTSC, region 1, Dolby digital.
Keywords: Science films; Weather -- Juvenile films; Children's television programs; Animated television programs; Science television programs; Educational television programs